An Image Encryption Scheme Based on Lorenz System for Low Profile Applications - Anees, Amir (3D research, 2015)
Advanced encryption standard being a benchmark for encryption is very ideal for digital images encryption for its security reasons but might not be effective for low profile applications due to its high computational and hardware complexity. In this paper, we presents a robust image encryption scheme for these types of applications based on chaotic sequences of Lorenz system, also ensuring the system security as well. The security strength is evident from the results of statistical and key analysis done in this paper.